Partisipasi Politik Masyarakat Difabel dalam Pembentukan Kebijakan Pendidikan Tinggi Inklusif - Fikri, Abdullah (INKLUSI, 2014)
Inclusive education is an educational syem that accessible for everybody in any condition. In this case, the focus of inclusive education is for people with disabilities. People with any disability have the same right to acquire formal education. Until now, inclusive education is implemented in the elementary and middle school level, so higher education inclusive paradigm still needs to get more attention.Inclusive higher education is a continuity of inclusive education in the elementary and middle school level. In a formal sense, inclusive education in college has not gotten the policy that affirm the implementation of inclusive education in the college level. Therefore, people with disabilities and disabled-people activits, either from academic or non-academic settings, need to undertake the political efforts to toward policy makers for making policy about implementation of inclusive education in the college nationally. Community’s efforts to influence government decision-making is called political participation. Political participation is a form of community involvement to influence the policy-making process. In this case, the public policy form is called (regeling), which is the result of cooperation betwwen the local government and the local parliament and so president and parliament.In the context of democracy, people with disabilities is one of the people who are the actors in policy making. Participation of the population occurs not only in the electoral process, but also other places. It means that people with disabilities who certainly have interests, which interests will only be actulized if they are involved in political participation. Those which are strategic to realize is related  with inclusive higher education by national policy instrument (UU). With the national policy, the rights of people with disability can be guaranted and protected to access the college.